Hospital cybersecurity risks and gaps: Review (for the non-cyber professional) - Wasserman, Liat; Wasserman, Yair (Frontiers in Digital Health, 2022)
Healthcare is facing a growing threat of cyberattacks. Myriad data sources illustrate the same trends that healthcare is one of the industries with the highest risk of cyber infiltration and is seeing a surge in security incidents within just a few years. The circumstances thus begged the question: are US hospitals prepared for the risks that accompany clinical medicine in cyberspace? The study aimed to identify the major topics and concerns present in today’s hospital cybersecurity field, intended for non-cyber professionals working in hospital settings. Via structured literature searches of the National Institutes of Health’s PubMed and Tel Aviv University’s DaTa databases, 35 journal articles were identified to form the core of the study. Databases were chosen for accessibility and academic rigor. 87 additional sources were examined to supplement the findings. The review revealed a basic landscape of hospital cybersecurity, including primary reasons hospitals are frequent targets, top attack methods, and consequences hospitals face following attacks. Cyber technologies common in healthcare and their risks were examined, including medical devices, telemedicine software, and electronic data. By infiltrating any of these components of clinical care, attackers can access mounds of information and manipulate, steal, ransom, or otherwise compromise the records, or can use the access to catapult themselves to deeper parts of a hospital’s network. Issues that can increase healthcare cyber risks, like interoperability and constant accessibility, were also identified. Finally, strategies that hospitals tend to employ to combat these risks, including technical, financial, and regulatory, were explored and found to be weak. There exist serious vulnerabilities within hospitals’ technologies that many hospitals presently fail to address. The COVID-19 pandemic was used to further illustrate this issue. Comparison of the risks, strategies, and gaps revealed that many US hospitals are unprepared for cyberattacks. Efforts are largely misdirected, with external - often governmental - efforts negligible. Policy changes, e.g., training employees in cyber protocols, adding advanced technical protections, and collaborating with several experts, are necessary. Overall, hospitals must recognize that, in cyber incidents, the real victims are the patients. They are at risk physically and digitally when medical devices or treatments are compromised.